ONTOLOGI DAKWAH (UPAYA MEMBANGUN KEILMUAN DAKWAH) - Syamsuri Syamsuri (Hunafa: Jurnal Studia Islamika, 2006)
Da’wah (Islamic mission) is an effort and a transformation of Islamic teachings. Many aspects such as sociology, politics, economy, culture, science, etc influence the process of da’wah. Multi-interpretation to the Islamic teachings has also brought about different experiences in implementing the Islamic teachings. This can be seen from the emergence of sects and religious movements in society. As a result, the activities of da’wah take place in various methods, either in individual method or in collective one. Kata Kunci : ontologi, dakwah